Investigating the Transformative Impact of the Family Hope Program (PKH) on Basic Needs and Community Development in Pardomuan I Village, Pangururan District, Samosir Regency - Sihotang, Demita; Sihotang, Marsono Mersel (Institute for Law and Economics Studies, 2022)
This research delves into the transformative influence of the Family Hope Program (PKH) on fulfilling basic needs in Pardomuan I Village, Pangururan District, Samosir Regency. Against the backdrop of Indonesia's social welfare initiatives, the study navigates the correlations and trends shaping economic empowerment, educational attainment, health outcomes, and women's empowerment within the community. Employing a mixed-methods research design, the study integrates quantitative surveys, in-depth interviews, focus group discussions, and documentary analysis to capture the multifaceted impact of PKH. A purposive sampling strategy targets PKH beneficiary families, ensuring diverse representation. Ethical considerations guide the research process, fostering transparency and participant trust. The research reveals robust correlations between PKH participation and economic empowerment, emphasizing the program's role as a financial lifeline, poverty alleviator, and catalyst for improved housing and food security. Educational outcomes showcase a positive association, linking PKH to increased school enrollment and attendance. Health initiatives correlate with enhanced well-being, and gender-inclusive strategies correlate with heightened economic resilience among women. Policy implications advocate for the expansion of targeted cash transfers, integrated health and education initiatives, and gender-inclusive strategies in social welfare programs. Practitioners are encouraged to adopt community-centric approaches, continuous monitoring, and adaptive strategies. Future research directions include longitudinal studies, comparative analyses, and exploring multi-program interactions